KELIMPAHAN JENIS DAN ESTIMASI PRODUKTIVITAS Ficus spp. SEBAGAI SUMBER PAKAN ALAMI ORANGUTAN SUMATERA (Pongo abelii) DI PUSAT PENGAMATAN ORANGUTAN SUMATERA (PPOS), TAMAN NASIONAL GUNUNG LEUSER - Santy DN Purba; Pindi Patana; Erni Jumilaty (Program studi Kehutanan USU, 2015)
Ficus spp. a feed source tree that is a keystone species for primates and birds. Availability Ficus spp feed. This needs to be evaluated. Therefore, the availability of this feed is quantified through Ficus spp abundance. and estimates of productivity growth in young leaves, fruits, and flowers Ficus spp. The methodology used in this research is the analysis of vegetation and Zweifel method. The results were obtained Ficus spp abundance. highest in saplings found in trail 1 (4.325). Ficus spp abundance. relatively rare. Estimated productivity of young leaves in the January to April period of observation ranges from 30% -40%. Estimated productivity of flowers in the period January to April tends to moderate. Estimated productivity of fruit in the January to April period of observation ranged from 1-100 pieces per month. Period fertilization occurs after the flowering period, so the number of pieces that appear influenced by the growing amount of interest. If the amount of interest a little, then the amount of fruit too little. Observation period of January to April, including not tend to dry the fruit season. Other species in ecological niches are black squirrels and hornbills. Keywords: Ficus spp., Zweifel, estimated productivity, species abundance, ecological niches.Keyword: species abundance, productivity estimation, Ficus spp, Sumatran Orangutan, Natural Feed, Gunung Leuser National Park